Myocardial native T1 mapping and extracellular volume quantification in asymptomatic female carriers of Duchenne muscular dystrophy gene mutations - Masárová, Lucia; Panovský, Roman; Pešl, Martin; Mojica-Pisciotti, Mary Luz; Holeček, Tomáš; Kincl, Vladimír; Juříková, Lenka; Máchal, Jan; Opatřil, Lukáš; Feitová, Věra (Orphanet journal of rare diseases, 2023)
BACKGROUND: Female carriers of dystrophin gene mutations (DMD-FC) were previously considered non-manifesting, but in recent decades, cardiomyopathy associated with muscular dystrophy and myocardial fibrosis has been described. Our study aimed to assess prospectively myocardial fibrosis in asymptomatic DMD-FC compared to a sex-matched control group (CG) with similar age distribution using native T1 mapping and extracellular volume (ECV) quantification by cardiovascular magnetic resonance (CMR) imaging. MATERIALS AND METHODS: 38 DMD-FC with verified genetic mutation and 22 healthy volunteers were included. Using CMR, native T1 relaxation time and ECV quantification were determined in each group. Late gadolinium enhancement (LGE) was assessed in all cases. RESULTS: There were 38 DMD-FC (mean age 39.1 ± 8.8 years) and 22 healthy volunteers (mean age 39.9 ± 12.6 years) imagined by CMR. The mean global native T1 relaxation time was similar for DMD-FC and CG (1005.1 ± 26.3 ms vs. 1003.5 ± 25.0 ms; p-value = 0.81). Likewise, the mean global ECV value was also similar between the groups (27.92 ± 2.02% vs. 27.10 ± 2.89%; p-value = 0.20). The segmental analysis of mean ECV values according to the American Heart Association classification did not show any differences between DMD-FC and CG. There was a non-significant trend towards higher mean ECV values of DMD-FC in the inferior and inferolateral segments of the myocardium (p-value = 0.075 and 0.070 respectively). CONCLUSION: There were no statistically significant differences in the mean global and segmental native T1 relaxation times and the mean global or segmental ECV values. There was a trend towards higher segmental mean ECV values of DMD-FC in the inferior and inferolateral walls of the myocardium.
Keywords: dospělí; Extracellular volume quantification; Humans; Mutation; lidé středního věku; myokard; Middle Aged; gadolinium; Gadolinium; Spojené státy americké; Late gadolinium enhancement; Duchenne muscular dystrophy; Adult; Native T1 mapping; ženské pohlaví; kontrastní látky; United States; Contrast Media; lidé; mutace; Muscular Dystrophy, Duchenne; Myocardium; Duchennova muskulární dystrofie; Cardiac magnetic resonance; Female